2014
DOI: 10.1007/s00249-014-1002-9
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin inhibits collagen fibril formation and increases the stability of collagen fibers

Abstract: Capsaicin is a versatile plant product which has been ascribed several health benefits and anti-inflammatory and analgesic properties. We have investigated the effect of capsaicin on the molecular stability, self-assembly, and fibril stability of type-I collagen. It was found that capsaicin suppresses collagen fibril formation, increases the stability of collagen fibers in tendons, and has no effect on the molecular stability of collagen. Turbidity assay data show that capsaicin does not promote disassembly of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…A few of the most antimicrobial spices [27] are commonly used in Indian cuisines. Our recent studies have shown the beneficial role of capsaicin, an active component in cayenne which was revealed to be the most prominent ingredient in consistently rendering the negative food pairing in all regional cuisines [28]. The importance of spices in Indian regional cuisines is also highlighted by the fact these cuisines have many derived ingredients (such as garam masala, ginger garlic paste etc.)…”
Section: Discussionmentioning
confidence: 98%
“…A few of the most antimicrobial spices [27] are commonly used in Indian cuisines. Our recent studies have shown the beneficial role of capsaicin, an active component in cayenne which was revealed to be the most prominent ingredient in consistently rendering the negative food pairing in all regional cuisines [28]. The importance of spices in Indian regional cuisines is also highlighted by the fact these cuisines have many derived ingredients (such as garam masala, ginger garlic paste etc.)…”
Section: Discussionmentioning
confidence: 98%
“…Fibril formation of type I collagen has been widely studied by some research teams. [40][41][42][43][44][45][46] Therefore, type I collagen was investigated in this present work to assess to what extent CQDs may inhibit its fibrillation. As explained in the experimental section, fibril formation of type I collagen was initiated by incubating collagen I solution at 37 °C.…”
Section: Inhibition Of Type I Collagen Aggregation With Cqd-1 and Cqd-2mentioning
confidence: 99%
“…While the role of capsaicin in fibrosis has been challenged, several studies have shown that capsaicin has proven antifibrotic properties ( Wang Q et al, 2014 ; Perumal et al, 2015 ; Choi et al, 2017 ; Mendivil et al, 2019 ; Sheng et al, 2020 ). Capsaicin activation of TRPV-1 increases intracellular calcium ([Ca 2+ ] i ), upregulates AMP-activated protein kinase (AMPK), and SIRT-1, which then upregulates endothelial nitric oxide synthase (eNOS) ( McCarty et al, 2015 ), thus improving the endothelium-dependent vasodilation (EDV).…”
Section: The Role Of Capsaicin As An Antifibrotic Agentmentioning
confidence: 99%